From interdisciplinarity to transdisciplinarity: new trends in the philosophy of science - Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The correlation between interdisciplinarity and transdisciplinarity and their methodological possibilities are analyzed.